PROMOSI DAN KUALITAS PRODUK DALAM MENDORONG KEPUTUSAN PEMBELIAN KONSUMEN - Muhamad Restu Wijaya; Dede Solihin (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2026)
This study aims to examine the role of promotion and product quality in driving consumer purchase decisions of Camille Beauty products at PT Shavira Barokah Utama. The research employed an associative method. The population consisted of all consumers who purchased Camille Beauty products at PT Shavira Barokah Utama, and the sample was determined using the Rao Purba formula, resulting in 96 respondents. Data analysis was conducted using multiple linear regression. The results show that promotion plays a very strong role in driving purchase decisions. This is indicated by the regression model, which demonstrates that an increase in promotional activities is followed by an increase in consumer purchase decisions. Furthermore, product quality also plays an important role in driving purchase decisions. The regression model indicates that improvements in product quality are followed by an increase in consumer purchase decisions.The simultaneous test results also indicate that both variables jointly have a significant effect on consumer purchase decisions of Camille Beauty at PT Shavira Barokah Utama. This confirms that promotion and product quality together are important factors in shaping consumer purchasing behavior.